2013
DOI: 10.2478/s11756-013-0182-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression analysis of glucose-regulated protein 78 (GRP78) gene in silkworm Bombyx mori

Abstract: GRP78 (78 kDa glucose-regulated protein), also known as BiP (immunoglobulin heavy-chain-binding protein), is an essential regulator of endoplasmic reticulum (ER) homeostasis because of its multiple functions in protein folding, ER calcium binding, and controlling of the activation of transmembrane ER stress sensors. In this report, we cloned the full-length cDNA of GRP78 from silkworm Bombyx mori (BmGRP78). It is 2645 bp, including an open reading frame (ORF) of 1977 bp encoding a polypeptide of 658 amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“… Zhu et al (2013) indicated that the expression of grp78 in the liver of grass carp Ctenopharyngodon idella was higher than other tissues. Other studies also indicated higher Grp78 accumulation in brain ( Higashino et al 2006 ; Xi and Ma 2013 ) and heart tissue in mammals ( Oh-hashi et al 2003 ). In the present study, crt mRNA was expressed ubiquitously in every tissue, with the highest in liver and the lowest in ovary, mid-intestine, gill, and skeletal muscle.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“… Zhu et al (2013) indicated that the expression of grp78 in the liver of grass carp Ctenopharyngodon idella was higher than other tissues. Other studies also indicated higher Grp78 accumulation in brain ( Higashino et al 2006 ; Xi and Ma 2013 ) and heart tissue in mammals ( Oh-hashi et al 2003 ). In the present study, crt mRNA was expressed ubiquitously in every tissue, with the highest in liver and the lowest in ovary, mid-intestine, gill, and skeletal muscle.…”
Section: Discussionmentioning
confidence: 79%
“…The present study indicated that grp78 mRNA levels were the highest in liver, followed by heart and brain. The noninduced level of expression of grp78 indicated that it might play multiple functions in yellow catfish as its homologs reported in other living organisms ( Xi and Ma 2013 ). Zhu et al (2013) indicated that the expression of grp78 in the liver of grass carp Ctenopharyngodon idella was higher than other tissues.…”
Section: Discussionmentioning
confidence: 88%
“…In the mammalian system, grp78 levels are regulated by various ER stress factors such as accumulation of unfolded proteins, intracellular calcium efflux, pathological conditions, and glucose deprivation (Lee, ; Shim et al., ). In other vertebrates, grp78 levels are also changed due to thermal and pathological stresses (Luan, Li, Zhang, Wang, & Xiang, ; Xi & Ma, ). These findings suggest that the downregulation of grp78 in the feeding stage larvae after envenomation might be attributed to the shortage of nutrition supply to the cells of host insects.…”
Section: Discussionmentioning
confidence: 99%
“…As with hsc70 , grp78 is not known to respond to thermal stress in vertebrates (Lee, ). However, in studies on invertebrate species, thermal stress is shown to induce grp78 in silkworms, shrimp and overwintering gall flies, although not in red mites (Luan et al ., ; Zhang et al ., ; Yang et al ., ; Xi & Ma, ). The present study demonstrates that significant changes in the grp78 levels of A. gossypii are not induced by exposure to 0–40 °C for 1 h. Thus, it is likely that the response of grp78 to thermal stress may vary among different species of invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…GRP78 and its gene ( grp78 ) exist in various invertebrate species, although their physiological roles are only described in a few species. As in other hsp genes, grp78 is upregulated by thermal stress and pathogen infection in the silkworm Bombyx mori and the Chinese shrimp Fenneropenaeus chinensis (Luan et al ., ; Xi & Ma, ). The level of GRP78 also increases along with other HSPs to provide freezing tolerance and winter survival of gall fly larvae ( Eurosta solidaginis ) (Zhang et al ., ).…”
Section: Introductionmentioning
confidence: 99%